AC Impedance Spectroscopy of CaF2‐doped AlN Ceramics. Issue 3 (13th December 2013) - Lee, Hyeon‐Keun; Lee, Hyun Min; Kim, Do Kyung; Chan, H.
<x xml:space="preserve">Abstract</x> The electrical conductivity of CaF2‐doped aluminum nitride (AlN) ceramics was characterized at high temperatures, up to 500°C, by AC impedance spectroscopy. High thermal conductive CaF2‐doped AlN ceramics were sintered with a second additive, Al2O3, added to control the electrical conductivity. The effects of calcium fluoride (CaF2) on microstructure and related electrical conductivity of AlN ceramics were examined. Investigation into the microstructure of specimens by TEM analysis showed that AlN ceramics sintered with only CaF2 additive have no secondary phases at grain boundaries. Addition of Al2O3 caused the formation of amorphous phases at grain boundaries. Addition of Al2O3 to CaF2‐doped AlN ceramics at temperatures 200°C–500°C revealed a variation in electrical resistivity that was four orders of magnitude larger than for the specimen without Al2O3. The amorphous phase at the grain boundary greatly increases the electrical resistivity of AlN ceramics without causing a significant deterioration of thermal conductivity.